DPred_3S: identifying dihydrouridine (D) modification on three species epitranscriptome based on multiple sequence-derived features - Ren, Jinjin; Chen, Xiaozhen; Zhang, Zhengqian; Shi, Haoran; Wu, Shuxiang (Frontiers in Genetics, 2023)
Dihydrouridine is a conserved modification of tRNA among all three life domains. D modification enhances the flexibility of a single nucleotide base in spatial structure and is disease-and evolution-associated. Recent studies have also suggested the presence of dihydrouridine on mRNA. To identify D in epitranscirptome, we provided a prediction framework named "Dpred_3S" based on machine learning approach for three species D epitranscriptome, which used epitranscirptome sequencing data as training data for the first time. The optimal features were evaluated by F score and different features integration; our model achieved AUROC scores 0.955, 0.946 and 0.905 for S.cerevisiae, E. coli and S. pombe, respectively. The performances of different machine learning algorithms were also compared in this study.